Apendektómia - porovnanie výsledkov laparoskopickej a otvorenej techniky operácie - Skrovina, M; Vanko, R; Czudek, S; Adamcík, L; Bartos, J; Velkoborský, M; Ivan, Ferák I (Rozhledy v chirurgii, 2007)
AIM: The authors present results of laparoscopy versus open appendectomy in patients indicated for urgent procedures. MATERIALS AND METHODS: 214 patients, who underwent urgent appendectomy during a 18-month period (November 2004 - April 2006) were included in the retrospective study. The subjects were assigned to two main study groups according to the chosen abdominal approach - laparoscopic versus classical method. Within the respective study groups, duration of the procedure, histopathological findings, peroperative and postoperative complications, duration of postoperative hospitalization were assessed. Furthermore, in the laparoscopic subgroup, requirement for conversion to open surgery is assessed. RESULTS: The results proved that the laparoscoic approach reduced hospitalization period in patients with histopathologicaly advanced findings. The positive effect of miniinvasive methods on hospitalization duration is diminished in subjects with less advanced findings. CONCLUSION: Considering overall benefits of the laparoscopic procedures, the authors themselves prefer the laparoscopic method as the method of choice in management of acute appendicitis.
Keywords: ženské pohlaví; Child; Female; Emergencies; apendektomie; lidé; Humans; dospělí; Laparoscopy; laparoskopie; dítě; Adult; Appendectomy; Male; mužské pohlaví; náhlé příhody